Aller, revenir, tisser un abri : Route One/USA, de Robert Kramer (1989) - Gilles Chamerois (Transatlantica)
Route One USA marks Robert Kramer’s brief return from exile. Mixing as usual documentary and fiction, the American filmmaker examines the country at the eve of the 1988 general elections. As Doc encounters various individuals and communities down Route One, Robert films him and diagnoses a society whose precise ailment is the incapacity to connect its discourse to the reality of its situation and of its history. But the film also attempts to offer remedies, and to re-instore relations between words and the territory so as to make it inhabitable again, even if its model is more Thoreau’s temporary cabin than any stately mansion.